FRI0337 Infliximab for sight-threatening and refractory uveitis of behçet's syndrome. (23rd January 2014) - Hamuryudan, V.; Hatemi, G.; Ozyazgan, Y.; Ucar, D.; Yurdakul, S.; Seyahi, E.; Tascilar, K.; Ugurlu, S.; Yazici, H.
Abstract : Background: Uncontrolled studies, mainly of short duration suggest that infliximab, an anti TNF agent, is beneficial in controlling severe uveitis of BS (1 ). Objectives: To evaluate the efficacy and safety of prolonged infliximab treatment in severe sight-threatening uveitis of BS. Methods: The charts of 43 BS patients (33 men; age at the initiation of infliximab: 31±8.4 SD years) treated with infliximab (5 mg/kg) were reviewed retrospectively. All patients had severe, sight-threatening posterior uveitis of long-duration (82±50 SD months) refractory to previous treatments with multiple immunosuppressives (azathioprine=43, Cyclosporin A=42, Interferon alfa=38; duration of treatment: 62±43 SD months) and steroids. Efficacy was assessed by the change of visual acuity (LogMAR VA) and the decrease in the number of attacks under infliximab. Results: The duration of infliximab treatment was 31±18 SD months (median 29 months). In 37 (86%) patients infliximab was combined with azathioprine (n= 26), azathioprine and cyclosporine A (n=10) or interferon alfa (n=1). Twenty-nine (67%) patients had no useful vision (LogMAR >1) in at least one eye at the time of initiation of infliximab. Five of them (17%) had gained useful vision of both eyes under infliximab. The mean VA (all patients) was maintained under infliximab (right eye: 0.83± 0.74 vs 0.84 ±0.79; left eye: 1.27±0.83 vs 1.13± 0.88). VA of the worse eye improved in 11 patients, remained stable in 24 and worsened in 8 patients. Eleven patients (26%) with no attacks during previous treatment were prescribed infliximab to protect the already compromised vision. The VA was stable or improved in 10 and 9 remained attack free. Of the 32 patients (74%) with attacks before infliximab, 11 (34%) became attack free under infliximab. The number of uveitis attacks per year (all patients) under previous immunosuppressive treatment dropped from 1.9 ±3 to 0.3 ±0.6 in the right eye ( p =0.0001) and from 2.5± 2.9 to 0.3 ±0.6 in the left eye ( p =0.0001). There was also a significant decrease in the numbers of patients with hypopyon (11 and 3; x 2 = 5.46, p=0.019), vascular infiltrations (23 and 12; x 2 = 5.83, p=0.016), macular edema (8 and 1; x 2 = 6.08, p=0.014), and retinal hemorrhages (7 and 0; x 2 = 7.62, p=0.006) under infliximab. Infliximab treatment was terminated in 16 patients (adverse events =5, inefficacy =1, terminal eye disease = 4, unrelated reasons = 6). Fifteen of these patients received further treatment (biologics = 3, azathioprine =12) for 22±13 SD months and 12 of them remained attack free during this period. The adverse events causing discontinuation were pulmonary tuberculosis in 3 (at 17. 32. and 46. month of infliximab treatment, respectively), depression in 1, pneumonia in1 patient. Conclusions: Infliximab combined with immunosuppressives was useful in preserving visual acuity and in controlling the attacks in BS patients with refractory, sight-threatening uveitis at the long-term. Relapses were infrequent after discontinuation. Tuberculosis appears as a concern in prolonged treatment. References: Arida A, et al. Semin Arthritis Rheum 2011; 41: 61. Disclosure of Interest : None Declared